Learning Strategies Used by English Students in Coping with Extensive Reading Assignments: A Mixed Method Approach - Apriani, Nia; Waluyo, Untung; Susanti, Mira; Zamzam, Ahmad (Journal of Authentic Research, 2025)
This study examines the learning strategies used by fourth-semester English students at the Faculty of Teacher Training and Education, University of Mataram, in coping with extensive reading assignments. Students face with too much materials and experience cognitive overload that makes them hard to process and remember what they have read. To address these issues, this research aimed to identify the specific strategies students use and evaluate their effectiveness in enhancing reading comprehension. A mixed-methods approach was applied, combining quantitative data from reading comprehension tests with qualitative data from interviews and observations. Forty students participated, representing varying proficiency levels. Descriptive statistics showed that students performed best in identifying main ideas (82%) and factual information (80%) but struggled with drawing conclusions (55%) and understanding vocabulary (60%). Thematic analysis of interviews showed that students commonly applied cognitive strategies such as note-taking, highlighting, summarizing, and mapping, along with metacognitive strategies including planning and time management. Quantitative data showed that students who tend to get high scores on reading comprehension tests use cognitive strategies, this is aligned with qualitative data from interviews and observations which explain that they use cognitive strategies to understand the text in depth. The results indicate that although students are proficient in lower-order strategies, they struggle with higher-order thinking abilities like evaluation and inference. In order to improve overall comprehension, the study emphasizes the important of teaching that focused on vocabulary development and critical reading. This study concludes that students’ independence, confidence, and performance in English reading tasks can be improved by incorporating explicit strategy training into comprehensive reading tasks. It contributes to the existing body of knowledge on language learning strategies, particularly in the context of extensive reading assignments in higher education.